2020
DOI: 10.1111/pai.13296
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses are associated with serum metabolome among infants hospitalized for bronchiolitis: A multicenter study

Abstract: Background: Bronchiolitis is the leading cause of infant hospitalizations in the United States. Growing evidence supports the heterogeneity of bronchiolitis. However, little is known about the interrelationships between major respiratory viruses (and their species), host systemic metabolism, and disease pathobiology. Methods: In an ongoing multicenter prospective cohort study, we profiled the serum metabolome in 113 infants (63 RSV-only, 21 RV-A, and 29 RV-C) hospitalized with bronchiolitis. We identified seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…Metabolic changes in plasma have been previously reported for different viral infections, such as SARS, 6 H1N1, 7 respiratory syncytial virus, 8 Ebola virus 9 and dengue. 10 Recent studies have revealed that metabolic dysregulation in COVID-19 patients and metabolites may help stratify patients in terms of disease severity during hospitalisation.…”
Section: Introductionmentioning
confidence: 83%
“…Metabolic changes in plasma have been previously reported for different viral infections, such as SARS, 6 H1N1, 7 respiratory syncytial virus, 8 Ebola virus 9 and dengue. 10 Recent studies have revealed that metabolic dysregulation in COVID-19 patients and metabolites may help stratify patients in terms of disease severity during hospitalisation.…”
Section: Introductionmentioning
confidence: 83%
“…However, in agreement with the current study, the emerging evidence on bronchiolitis suggests the complexity in the disease pathobiology, reflected by heterogeneous host transcriptome, 11,12 microRNA, 11 cytokine, 13 and upper airway microbiome 10,33 profiles among infants with bronchiolitis. Additionally, recent studies have individually applied a metabolomic approach to each of the upper airway 14,34 and serum 15,35 sample, and reported between‐virus (and viral species) differences in the metabolic pathways in infants with bronchiolitis. Interestingly, these studies have shown that the discriminatory metabolites differ between the airway and circulating systems; however, their integrated relationship remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This was especially true of the severe and critical COVID-19 patients. 8,9,32 Therefore, we hypothesize that these metabolic disruptions in the recovered COVID-19 patients might also result from damages caused by COVID-19 viruses. The elevation of bile acid derivatives, such as chenodeoxycholic acid (CDCA), glycochenodeoxycholate-3-sulfate (GCDCS) in the plasma of recovered patients, compared with HC, may indicate hepatic detoxi cation function was impaired and biliary ducts were injured.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecular metabolites, as the downstream products of genes and proteins, are closely related to the phenotype, and can accurately re ect subtle changes and potential impact under the biological state. 5 Metabolic changes in plasma have been previously reported for different viral infections, such as infection with SARS, 6 H1N1, 7 respiratory syncytial virus, 8 Ebola virus 9 and dengue. 10 Recent studies revealed metabolic dysregulation in COVID-19 patients and metabolites may help stratify patients in term of disease severity during hospitalization.…”
Section: Introductionmentioning
confidence: 92%